2019
DOI: 10.3389/fphys.2019.00404
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrate Supplementation Improves Exercise Tolerance by Reducing Muscle Fatigue and Perceptual Responses

Abstract: The present study was designed to provide further insight into the mechanistic basis for the improved exercise tolerance following dietary nitrate supplementation. In a randomized, double-blind, crossover design, twelve recreationally active males completed a dynamic time-to-exhaustion test of the knee extensors after 5 days of consuming both nitrate-rich (NITRATE) and nitrate-depleted beetroot juice (PLACEBO). Participants who improved their time-to-exhaustion following NITRATE performed a time-matched trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 83 publications
3
37
0
1
Order By: Relevance
“…This study also found that no mean differences were observed for fastest sprint time or fatigue index after BRJ consumption (Clifford, Bell, et al 2016;Clifford, Berntzen, et al 2016). Some studies have shown a reduction in muscle pain and fatigue associated with exercise induced muscle damage and reduced after with BRJ supplementation Husmann et al 2019). Furthermore, Clifford, Bell, et al (2017) published a study which stated that supplementation of nitrate rich BRJ does not negatively influence acute muscular adaptations after eccentric exercise (Clifford, Bell, et al 2017).…”
Section: Effects Of Short-term Brj Supplementation In Relation To Trasupporting
confidence: 47%
See 1 more Smart Citation
“…This study also found that no mean differences were observed for fastest sprint time or fatigue index after BRJ consumption (Clifford, Bell, et al 2016;Clifford, Berntzen, et al 2016). Some studies have shown a reduction in muscle pain and fatigue associated with exercise induced muscle damage and reduced after with BRJ supplementation Husmann et al 2019). Furthermore, Clifford, Bell, et al (2017) published a study which stated that supplementation of nitrate rich BRJ does not negatively influence acute muscular adaptations after eccentric exercise (Clifford, Bell, et al 2017).…”
Section: Effects Of Short-term Brj Supplementation In Relation To Trasupporting
confidence: 47%
“…Since the metabolic perturbations occurring in (mainly type II) muscle fibers may be linked to the fatigue process, BRJ may delay the onset of fatigue by increasing PO 2 mv (Ferguson et al 2015). Indeed, Hoon et al (2015) found that four-day BRJ supplementation in healthy individuals decreased muscular fatigue in conditions of reduced blood flow during exhaustive exercise (Hoon et al 2015), and Husmann et al (2019) found reduced perceived effort and muscle pain after five-day BRJ ingestion (Husmann et al 2019). Additionally, several studies have found that BRJ improves exercise tolerance or rate of perceived exhaustion in normoxia (Aucouturier et al 2015;Bailey et al 2015;Balsalobre-Fern andez et al 2018;Breese et al 2013;Wylie, Kelly, Fulford, et al 2013) as well as hypoxia (Kelly et al 2014;Vanhatalo et al 2011).…”
Section: General Effects Of Brj On Skeletal Muscles and Oxygen Consummentioning
confidence: 99%
“…Several studies have assessed the effect of BJ supplementation on RPE. Although some authors have reported improved performance without any significant impact on RPE [ 12 , 14 , 55 ], others have shown lower RPE values [ 56 , 57 , 58 ]. To the authors’ knowledge, there is only one study that recorded the effect of BJ on RPE during RT [ 14 ]; Mosher et al [ 14 ] found that RPE during muscular endurance in RT was not significantly affected by 6 days of dietary nitrate supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrite is then converted to NO and nitrogen oxides in blood and tissues via multiple pathways (Bryan, 2006). Many studies have demonstrated the benefits of dietary nitrate, which may boost the nitrate-nitrite-NO pathway in the body (Lundberg et al, 2011a;Sindler et al, 2014b;Husmann et al, 2019). This distinct alternative pathway for NO generation is independent of NO synthase (NOS).…”
Section: Discussionmentioning
confidence: 99%